2014
DOI: 10.1016/j.nbd.2014.05.032
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of human uncoupling protein 2 (hUCP2) requires cAMP-dependent protein kinase in a toxin model of Parkinson's disease

Abstract: Parkinson's disease (PD), caused by selective loss of dopaminergic (DA) neurons in the substantia nigra, is the most common movement disorder with no cure or effective treatment. Exposure to the mitochondrial complex I inhibitor rotenone recapitulates pathological hallmarks of PD in rodents and selective loss of DA neurons in Drosophila. However, mechanisms underlying rotenone toxicity are not completely resolved. We previously reported a neuroprotective effect of human uncoupling protein 2 (hUCP2) against rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Although the mechanism by which UCP2 is activated by ROS is not completely understood, reactive aldehydes derived from lipid peroxidation have been suggested to be the ROS able to induce UCP2 activation [ 28 ]. The known intracellular signaling pathways mediating UCP2 gene activation are the AMPK/SIRT1/PPAR α axis [ 29 ] and the cAMP-dependent protein kinase [ 30 , 31 ].…”
Section: Ucp2 and The Pathogenesis Of Vascular Diseasesmentioning
confidence: 99%
“…Although the mechanism by which UCP2 is activated by ROS is not completely understood, reactive aldehydes derived from lipid peroxidation have been suggested to be the ROS able to induce UCP2 activation [ 28 ]. The known intracellular signaling pathways mediating UCP2 gene activation are the AMPK/SIRT1/PPAR α axis [ 29 ] and the cAMP-dependent protein kinase [ 30 , 31 ].…”
Section: Ucp2 and The Pathogenesis Of Vascular Diseasesmentioning
confidence: 99%
“…In addition to affects on cellular Ca 2+ signaling, neuronal UCPs may also influence other prominent signaling pathways including the cyclic AMP pathway. Thus, overexpression of UCP2 protected cultured primary dopaminergic neurons against the mitochondrial Complex I inhibitor rotenone, by a mechanism involving cyclic AMP-dependent protein kinase [51]. …”
Section: Mitochondrial Uncoupling Proteins and Neuroprotectionmentioning
confidence: 99%
“…For instance, Dagda et al (Dagda, et al 2011) demonstrated that treatment of PINK1 deficient SH-SY5Y cells with pharmacological PKA activators or transient expression of a constitutively active form of mitochondrially-targeted PKA or D-AKAP1 reversed mitochondrial fragmentation. In a recent study, Hwang et al, (Hwang, et al 2014) reported that the mitochondrial membrane transport protein human uncoupling protein 2 (hUCP2) protected dopamine neurons in adult flies against rotenone -mediated mitochondrial fragmentation and toxicity by increasing intracellular cAMP levels. On the other hand, PKA inhibitors blocked the preserved mitochondrial integrity, movement, and cell survival induced by hUCP2 in hUCP2-expressing dopamine neurons exposed to rotenone.…”
Section: Pka Dysregulation In Neurodegenerative Disordersmentioning
confidence: 99%